Impact of Social Media on Consumer Behavior: A Case in Kathmandu Valley - Bista, Puja; Rawat, Ramesh (Nepalese Journal of Management, 2024)
This study examines the impact of social media on consumer behavior in Kathmandu Valley. The dependent variable is consumer behavior. The selected independent variables are price, accuracy, time, income, advertisement and technology. The primary sources of data is used to assess the opinions of respondents regarding price, accuracy, time, income, advertisement and technology. The study is based on primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of social media on consumer behavior: A case in Kathmandu Valley. The study showed that price is positively correlated to the consumer behavior. It indicates that increasing in price leads to change in consumer behavior. Similarly, accuracy is positively correlated to the consumer behavior. It indicates that better accuracy stimulates the consumer behavior. Likewise, time is positively correlated to the consumer behavior. It indicates that better time can stimulates the consumer behavior. Further, income is positively correlated to the consumer behavior. It indicates that higher level of income leads to change in consumer behavior. Likewise, advertisement is positively correlated to the consumer behavior. It implies that increase in advertisement leads to change in consumer behavior. In addition, technology is positively correlated to the consumer behavior. It means that use of advanced and modern technology leads to change in consumer behavior.